Does Anti-corruption Policy Influence Energy Efficiency in China? - Liu, Jie; Guo, Jianming; Liu, Xiangfeng; Bai, Xiao; Taghizadeh-Hesary, Farhad (Frontiers in Energy Research, 2021)
The Chinese government has stepped up its anti-corruption efforts since 2013; the National Energy Administration, an energy regulatory agency, has since become a hard-hit area for corruption. This study analyzes the impact of government corruption on energy efficiency from the perspective of energy regulation. It analyzes the impact mechanism of corruption on energy efficiency and then adopts statistical methods to estimate the impact of corruption on China’s energy efficiency. The results show that government corruption has a generally negative effect on China’s energy efficiency. The establishment of dispatched energy regulatory agencies in eastern China can significantly reduce the adverse effects of corruption on energy efficiency. Furthermore, a single threshold effect was found between corruption and energy efficiency. Finally, based on the results of the empirical analysis, constructive policy suggestions are put forward.